Quality of life after two sequences of total neoadjuvant treatment in patients with locally advanced rectal cancer in the randomized CAO/ARO/AIO-12 phase 2 trial: clinical investigation - Kosmala, Rebekka; Hammann, Adriana Salazar; Paulus, Patrick; Zimmermann, Marcus; Wittig-Sauerwein, Andrea; Germer, Christoph-Thomas; Ghadimi, Michael; Hofheinz, Ralf-Dieter; Diefenhardt, Markus; Fokas, Emmanouil; Rödel, Claus; Polat, Bülent (International journal of radiation oncology, biology, physics, 2025)
Purpose - In a multicenter phase 2 trial the sequence of chemoradiation therapy (CRT) followed by consolidation chemotherapy (CT) before total mesorectal excision demonstrated higher pathological complete response rates than induction CT before CRT. Here, we present findings on quality of life (QoL). - Methods and Materials - Patients with rectal carcinoma (cT3-4 cN0-2) were randomly assigned to group A (CT + CRT; N = 156) or group B (CRT + CT; N = 150). This is a secondary QoL analysis (European Organization for Research And Treatment of Cancer QLQ-C30 + CR29, Wexner) before and during treatment and of disease-free patients during follow-up. - Results - At baseline, completed questionnaires were available for 86% (N = 134/156; group A) and 89% (N = 133/150; group B) of participants, with availability decreasing to 73% versus 64% at 1 year, 61% versus 59% at 2 years, and 51% versus 47% at 3 years. Global health status remained stable in both groups (range, 0-100) with baseline scores of 65.2 (mean, SD = 21.5; N = 133; group A) and 64.7 (SD = 23.2; N = 131; group B) and with scores of 67.6 (SD = 18.4; N = 52) and 65.4 (SD = 22.2; N = 46), respectively, at 3 years. No statistically or clinically relevant differences were observed between groups in any QoL scale on treatment completion or during follow-up. Both groups experienced declines in role functioning, body image, male erectile dysfunction, and stool incontinence (Wexner), which did not fully recover over the follow-up period. Rectal blood/mucus discharge and anxiety improved during treatment. - Conclusions - QoL did not differ between the 2 total neoadjuvant treatment sequences. QoL domains with long lasting deterioration may serve as endpoints in future studies focused on organ preservation.